The role of physical fitness on the relationship between motor competence and physical activity: mediator or moderator? - Lopes, Vitor P. (2022)
Understanding the mechanisms associated with engaging in physical activity (PA) is crucial for its promotion. The aim was to analyze the relationship between motor competence (MC) and PA and the role of physical fitness (PF). Participants were N = 1,064 children of both sexes (n =530 girls) and 7.87 +/- 1.17 years of age. MC was assessed with KorperkoordinationTest fur Kinder. PF was assessed with 50-yard dash, I-mile run/walk, and standing long jump. PA was assessed with a questionnaire. Mediation and moderation were determined according to Baron and Kenny using Sobel test for indirect effect and using PROCESS (version 3.4). Mediation results showed perfect mediation in girls but not in boys and not when all participants were included in the analysis. The linear moderation was significant for all participants and for boys and girls apart. However, the results of conditional effects of MC at the 16th, 50th, and 84th percentile of the PF, which became significant at the 50th percentile for all participants and for boys, were not significant in girls. In conclusion, perfect mediation seems to exist in girls but not in boys. In boys, the relationship between MC and PA seems conditioned by the PF levels.